Influence of Boron as a Heteroatom on Six Membered Borabenzenes - Dezfooli, Sahar (Asian Journal of Chemistry, 2012)
Boron is an important bridge between classic inorganic and organic chemistry. The heterocycle derivatives of boron are used extensively in synthesis, the effort on investigation of these compounds can be pioneer. In this research, an ab Initio method by using 6-31G+ basis set was applied to consider the influence of boron atoms on stability and aromaticity character of some borinine compared with benzene.